The Dynamics of Public Speaking Anxiety and its Impact on Speaking Performance: A Study Among College Students in Business and Economics - Megawati, Megawati; Apriani, Tia (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research investigates the relationship between public speaking anxiety and students’ speaking performance across various disciplines at a Business and Economics Institute. The primary question at the core of this study is whether there is a correlation between the level of public speaking anxiety and students’ speaking performance. The results of surveys and correlation analysis reveal a significant connection between the level of public speaking anxiety and students’ speaking performance. Students with higher anxiety tend to exhibit lower speaking performance. Factors affecting public speaking anxiety, such as preparation, audience size, presentation type, and target audience, are also analyzed. These findings provide additional insights into the impact of these factors on anxiety levels. Furthermore, the research identifies strategies and support programs to address public speaking anxiety and enhance students’ speaking abilities. These include training programs, psychological support, and communication courses. Recommendations involve developing more effective support programs and further research into the factors influencing public speaking anxiety. This study offers a deep understanding of the complexity of public speaking anxiety in the context of higher education, serving as a foundation for the development of educational programs that can improve students’ speaking skills and help them succeed in academic and professional situations.